Feasibility and acceptability of conducting a birth cohort study during the COVID-19 pandemic: a mixed-methods study - Allison M. Grech; Nathalie Kizirian; Marjan Mosalman Haghighi; Sweekriti Sharma; Reeja Nasir; Roslyn Muirhead; Angelika Zankl; Clare Collins; Andrew Holmes; Adrienne Gordon (BMC Pregnancy and Childbirth)
Abstract Background “BABY1000” was a pilot prospective birth cohort study based in Sydney, Australia, which aimed to identify factors before and during pregnancy that impact child and long-term health and assess study feasibility and acceptability. The COVID-19 pandemic and associated public health orders affected study protocols. This sub-study aimed to explore feasibility and acceptability of BABY1000 within this context. Methods Recruitment of women commenced before conception or during early pregnancy attending clinics at a major hospital in Sydney. Data collection extended from recruitment, across pregnancy at 12-, 20-, 28- and 36-weeks’ gestation, and postnatally (in both mothers and children) until the child’s second birthday. Feasibility was assessed using routinely collected data on recruitment, retention, and completion. BABY1000 participants were invited to complete an online acceptability survey, including the State-Trait Anxiety Inventory, and to participate in focus group discussions. Paired t-tests were used to compare sub-study respondents to the wider cohort of participants to assess for demographic drivers of feasibility. Chi-squared tests were used to examine associations between high anxiety and demographic characteristics, study acceptability, and the perceived impact of COVID-19 on study participation. Results From 225 women recruited, 180 (80%) remained enrolled at the end of pregnancy, with 100 (44%) remaining in the study until 24-months. Participant retention and data completeness were most challenging after birth. Eighty-seven mothers completed the acceptability survey and 22 parents participated in focus groups. Most participants found the study protocol to be acceptable and comfortable. A “high” anxiety score was not associated with study acceptability or willingness to participate, although metrics of both feasibility and acceptability were negatively impacted by the COVID-19 pandemic. Conclusions Whilst public health orders associated with the COVID-19 pandemic impacted feasibility and acceptability of the BABY1000 cohort, this sub-study found it is both feasible and acceptable to collect comprehensive biological, questionnaire, and health data from early pregnancy to two years. Study designs which tailor resources to where participant attrition can be predicted and have capacity to adapt to changing circumstances will be best placed to contribute to understanding of the Developmental Origins of Health and Disease.